Development and evaluation of praziquantel solid dispersions in sodium starch glycolate - Chaud, Marco V.; Lima, Andréa C.; Vila, Marta M.D.C.; Paganelli, Maria O.; Paula, Fábio C.; Pedreiro, Liliane N.; Gremião, Maria P.D. [UNESP] (African Journals Online (AJOL), 2013)
Purpose: To develop and characterize solid dispersions of praziquantel (PZQ) with sodium starch glycolate (SSG) for enhanced drug solubility. Methods: PZQ solid dispersion (SD) was prepared using co-precipitation method by solvent evaporation. The ratios of PZQ to SSG were 2:1, 1:1, 1:2, 1:3 (w/w). PZQ solubility was evaluated in purified water, and PZQ dissolution test was carried out in 0.1N HCl. Structural characterization of the dispersions was accomplished by x-ray diffraction (XRD) and infrared spectroscopy (FTIR) while the external morphology of the SDs, SSG and PZQ were studied by scanning electron microscopy (SEM). Mucoadhesion properties of the SD (1:3) and SSG, on mucin disks were examined using texture profile analysis. Results: The highest solubility was obtained with 1:3 solid dispersion, with PZQ solubility of 97.31 %, which is 3.65-fold greater than the solubility of pure PZQ and physical misture (PM, 1:3). XRD results indicate a reduction in PZQ crystallinity while infrared spectra showed that the functional groups of PZQ and SSG were preserved. SEM showed that the physical structure of PZQ was modified from crystalline to amorphous. The amount of PZQ in PM and SD (1:3) that dissolved in 60 min was 70 and 88 %, respectively, and these values increased to 76 and 96 %, respectively. The solid dispersion reduced the mucoadhesive property of the glycolate. Conclusion: Solid dispersion formulation using SSG is a good alternative approach for increasing the dissolution rate of PZQ. © Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, 300001 Nigeria. All rights reserved.
Keywords: Co-precipitation; Drug bioavailability; Praziquantel; Schistosomiasis; Sodium starch glycolate; Solid dispersion; hydrochloric acid; mucin; praziquantel; solvent; starch glycolate sodium; water; crystal structure; dispersion; drug bioavailability; drug release; drug screening; drug solubility; drug structure; evaporation; in vitro study; infrared spectroscopy; mucoadhesion; precipitation; scanning electron microscopy; X ray diffraction